2020
DOI: 10.1186/s12936-020-03336-z
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology and neurologic sequelae of cerebral malaria

Abstract: Cerebral malaria (CM), results from Plasmodium falciparum infection, and has a high mortality rate. CM survivors can retain lifelong post CM sequelae, including seizures and neurocognitive deficits profoundly affecting their quality of life. As the Plasmodium parasite does not enter the brain, but resides inside erythrocytes and are confined to the lumen of the brain's vasculature, the neuropathogenesis leading to these neurologic sequelae is unclear and underinvestigated. Interestingly, postmortem CM patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 145 publications
(210 reference statements)
1
63
0
9
Order By: Relevance
“…Severe malaria carries high mortality rates [ 91 , 92 ] due to complications as metabolic disorders, kidney failure, liver and lung disorders, anemia, and CM [ 93 96 ]. Cerebral malaria may lead to neurological complications (seizures, delirium, and coma) as well as cognitive deficits in survivors [ 97 ] and is the leading cause of non-traumatic encephalopathy in endemic regions. Non-cerebral malaria may also impact the brain, leading to cognitive and behavioral deficits [ 17 , 98 101 ].…”
Section: Malariamentioning
confidence: 99%
See 1 more Smart Citation
“…Severe malaria carries high mortality rates [ 91 , 92 ] due to complications as metabolic disorders, kidney failure, liver and lung disorders, anemia, and CM [ 93 96 ]. Cerebral malaria may lead to neurological complications (seizures, delirium, and coma) as well as cognitive deficits in survivors [ 97 ] and is the leading cause of non-traumatic encephalopathy in endemic regions. Non-cerebral malaria may also impact the brain, leading to cognitive and behavioral deficits [ 17 , 98 101 ].…”
Section: Malariamentioning
confidence: 99%
“…The pathophysiology of CM involves apoptosis of endothelial cells, BBB rupture, and subsequent neuroinflammation [ 97 ], related to an exacerbated systemic inflammation associated with parasite presence and release of toxic molecules, such as heme and hemozoin [ 101 105 ]. Additionally, the neurological complications of CM suggest abnormalities in neurotransmitter release.…”
Section: Malariamentioning
confidence: 99%
“…The neuropathogenesis of CM involves brain intravascular sequestration of P. falciparum -parasitized red blood cells occurring through the expression of parasite-encoded P. falciparum erythrocyte membrane protein-1 (PfEMP-1) in protuberances of the infected red-cell surface that interacts with host adhesion receptors on endothelium, contributing to the inflammatory process ( Lau et al., 2015 ). These events participate in the generation of blood flow impairment, endothelial dysfunction, intravascular coagulation, vascular occlusion, cerebral hypoxia, microglial activation, astrogliosis, disruption of the blood-brain barrier and neurotoxicity ( Medana et al., 2002 ; Taylor et al., 2004 ; Dorovini-Zis et al., 2011 ; Schiess et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…XRCC5, the gene encoding the KU80 protein, which plays a role in the repair of DNA doublestrand breaks (Grabsch et al, 2006), is up-regulated in cerebral patients in comparison with non-cerebral ones. This indicates a DNA-damage response by the host in response to cerebral malaria infection that may explain some of the long-term effects of cerebral malaria such as neurocognitive defects seen in survivors (Schiess et al, 2020). Both Senataxin (SETX) and MORC Family CW-Type Zinc Finger 2 (MORC2) are associated with a number of neurological disorders including cerebellar ataxia (Coutelier et al, 2018) and Charcot-Marie-Tooth disease (CMT) (Sevilla et al, 2016), however, SETX was also found to decrease the expression of anti-viral genes like INF-b delaying the infection resolution (Miller et al, 2015).…”
Section: Discussionmentioning
confidence: 96%